The meeting of a psychoanalyst and an indigenous healer: Sachs, W (1996) Black Hamlet. Johannesburg: Witwatersrand University Press. 340 pages. ISBN 1-86814-299-X - Sodi, Tholene (PINS-Psychology in Society, 2026)
Black Hamlet is an intriguing biography of a Zimbabwean immigrant who moved to South Africa in the 1920s. When it was published in 1937, Black Hamlet was hailed as a pioneering work in the genre of psychoanalytic biographies, more especially because a person of African descent was its subject of study. In 1947 the book was republished in a revised edition called Black anger. In this revised edition, Sachs subtly tried to rewrite the history of his own investigation to reflect a more politically sensitive attitude towards the African people. In the 1996 reprint of the 1937 edition, Sachs's original opinionated and rough style to describe the life of a black man from the perspective of a white man in South Africa is evident.